Proposal for new best estimates of the soil-to-plant transfer factor of U, Th, Ra, Pb and Po - Vandenhove, H. (2009)
There is increasing interest in radiological assessment of discharges of naturally occurring radionuclides into the terrestrial environment. Such assessments require parameter values for the pathways considered in predictive models. An important pathway for human exposure is via ingestion of food crops and animal products. One of the key parameters in environmental assessment is therefore the soil-to-plant transfer factor to food and fodder crops. The objective of this study was to compile data, based on an extensive literature survey, concerning soil-to-plant transfer factors for uranium, thorium, radium, lead, and polonium. Transfer factor estimates were presented for major crop groups (Cereals, Leafy vegetables, Non-leafy vegetables, Root crops, Tubers, Fruits, Herbs, Pastures/grasses, Fodder), and also for some compartments within crop groups. Transfer factors were also calculated per soil group, as defined by their texture and organic matter content (Sand, Loam, Clay and Organic), and evaluation of transfer factors' dependency on specific soil characteristics was performed following regression analysis. The derived estimates were compared with estimates currently in use.